Balanced Nutrition Education in School-Age Children: A Community Service - Rizqie Putri Novembriani; Nina Rini Suprobo; Elisa Danik Kurniawati; Winny Kirana Hasanah (STIKes Kepanjen, 2022)
Investing in child nutrition is critical to human resource quality because nutrition is a source of future growth, cognitive development, academic performance, and productivity. Nutrition education is one of the efforts to promote a healthy diet for life and should be started as early as possible. This community service activity aims to increase the understanding and awareness of school-age children regarding balanced nutrition. This activity was carried out at the Sobyor Nature School, Tulungrejo Village, Bumiaji District, Batu City, East Java. The results of the activity showed an increase in the knowledge score of the participants after health education was carried out using the method of lectures, discussions, and puzzle games. More community service activities involving parents and schools are expected to expand health education efforts.